(untitled) (TAMADDUN NURI JURNALI, 2024)
In this article, an opinion is expressed about the scientific heritage of Jadids, which came to the field of history as an educational, socio-political movement at the end of the XIX th century and the beginning of the XX th century. It is noted that the scientific and educational heritage of the ancients is similar to the educational policy implemented in Uzbekistan today.